Risk factors and management of breast cancer-related lymphedema - Alawad, Awad; Ibrahim, Ayat Omer (International Journal of Medicine, 2015)
Background: Lymphedema is a highly prevalent condition in women who have undergone treatment for breast cancer. Lymphedema negatively affects the quality of life.Objective: The aim of this study was to identify the clinical presentation of lymphedema associated factors in women treated for breast cancer.Methods:The study is an interventional prospective study. It was accomplished in the period from May 2013 to April 2014. Patients having breast cancer ipsilateral arm lymphedema were selected for the study.Results: A total of 34 patients were included in the study.73.5% of patients have a body mass index (BMI) of 25 or more at diagnosis. 70.6% of the patients underwent axillary clearance. All the patients did not undergo breast reconstruction. 52.4% had <10 lymph nodes removed from their axillae. 47% received radiotherapy. All patients presented with arm swelling, additionally, 70.6 % presented with arm heaviness 26.5% presented with arm pain. Elevation was effective in 90.5% of the compliant patients, while exercise was effective in 84.2% of the compliant patients.Conclusion: Breast cancer- related lymphedema continues to be a significant problem following breast cancer therapy. Presence of co-morbid conditions axillary radiation significantly increases the risk of lymphedema. A combination of axillary dissection axillary radiation should be avoided whenever feasible to avoid lymphedema.